Safety Measures Assessment is An Important Step Towards Guest Satisfaction Main Constraints Towards Current Pandemic Situation - Harshit Riat (AG Volumes, 2021)
The success of every company is directly tied to how well it serves its clients. When a company is just getting off the ground, consumers always come "first," followed by profit. One of the most critical strategic mechanisms in best-practice hotel organisations is the ability to keep customers happy. In order to create and sustain consumer satisfaction, business leaders and workers are constantly confronted with new obstacles. We want to find and develop metrics that may be utilised in the hotel sector to evaluate customer satisfaction and customer service performance, particularly in light of the present epidemic. The hotel industry's newest trends are also covered in this article.